2002
DOI: 10.1152/ajpheart.00733.2001
|View full text |Cite
|
Sign up to set email alerts
|

Acute exercise reduces the response to colon distension in T5 spinal rats

Abstract: .-Individuals with spinal cord injuries above thoracic level 6 (T 6) experience life-threatening bouts of hypertension, termed autonomic dysreflexia (AD). AD is mediated by peripheral ␣-adrenergic receptor supersensitivity as well as a reorganization of spinal pathways controlling sympathetic preganglionic neurons. A single bout of dynamic exercise may be a safe therapeutic approach to reduce the severity of AD because mild-to-moderate dynamic exercise reduces postexercise ␣-adrenergic receptor responsiveness,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 29 publications
0
19
0
Order By: Relevance
“…Peripheral noradrenaline supersensitivity has been documented in chronic human SCI (Mathias et al, 1976;Arnold et al, 1995), and there is additional evidence for more noradrenaline release per impulse (Gao et al, 2002) as well as an increased number of peripheral receptors post SCI (Velasco et al, 1997). In rats, approximately 50% of the AD pressor response can be attributed to vascular hyper-responsiveness (Collins and DiCarlo, 2002). At present it is difficult to determine the relative contribution of increased sympathetic outflow and peripheral noradrenaline supersensitivity on conductance changes in the current study.…”
Section: Discussionmentioning
confidence: 82%
“…Peripheral noradrenaline supersensitivity has been documented in chronic human SCI (Mathias et al, 1976;Arnold et al, 1995), and there is additional evidence for more noradrenaline release per impulse (Gao et al, 2002) as well as an increased number of peripheral receptors post SCI (Velasco et al, 1997). In rats, approximately 50% of the AD pressor response can be attributed to vascular hyper-responsiveness (Collins and DiCarlo, 2002). At present it is difficult to determine the relative contribution of increased sympathetic outflow and peripheral noradrenaline supersensitivity on conductance changes in the current study.…”
Section: Discussionmentioning
confidence: 82%
“…paraplegia have elevated heart rates (23), increased blood pressure variability (71), episodic bouts of life-threatening hypertension as part of a condition termed autonomic dysreflexia (12,13), and elevated sympathetic activity above the level of the lesion (14,31,48,70). Paraplegia also alters cardiac electrophysiology and the abundance of Ca 2ϩ regulatory proteins in a manner that increases the susceptibility to electrically-induced as well as ischemia and reperfusion-induced ventricular arrhythmias (14,48,49,70,71).…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, only two studies have investigated the effect of exercise on cardiovascular function in animals with SCI. Collins et al 131 reported that acute (1 bout) treadmill exercise reduced the severity of AD induced via colorectal distension. Although those authors attributed this reduction in AD severity to an exerciseinduced reduction in a-adrenoceptor hypersensitivity, no measures of hypersensitivity were included in their experimental design; hence, the mechanistic basis for the acute reduction in AD severity could not be determined.…”
Section: Deconditioning-induced Alterations In Vasculaturementioning
confidence: 99%